Beneath the Teaching Iceberg: Exposing the Hidden Support Dimensions of Indigenous Academic Work - Page, Susan; Asmar, Christine (The Australian Journal of Indigenous Education, 2008)
Abstract Indigenous students everywhere are known to require particular types and levels of support as they enter, and continue their studies within universities. Such support is often provided by designated support workers employed for that purpose. Our study of Aboriginal and Torres Strait Islander academic staff around Australia, however, found that teaching staff also spend considerable time and effort supporting their students' learning experiences both in and out of the classroom. Our findings suggest that this issue is multi-dimensional and complex. Outwardly, visible dimensions of Indigenous academic support roles, we found, are often just the tip of an iceberg. We argue that, while students' need for support is increasingly well documented, the informal support roles played by the few Indigenous academics have been under-reported and may not be visible, or recognised. Going further, we propose a new conceptual framework for analysing the unique context in which Indigenous academic work occurs.